Validity of inquiry-based nutrition topic module to train critical thinking skills by accommodating cognitive style - Siti Zubaidah; Imas Cintamulya (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The inquiry-based nutrition topic module was developed so that it can be used as an alternative innovative learning media and is expected to accommodate students' learning needs based on cognitive style. This study aims to design an inquiry-based nutrition topic module to train valid critical thinking skills. This study used the 4D research and development model but only reached the product validity stage. The initial stage (define) carried out the MFFT test in class VIIIA SMPN 2 Jenu, the results were 11 students with a reflective cognitive style and 11 students with an impulsive cognitive style. Based on the results of the MFFT test, the design of the inquiry-based nutrition topic module was designed to accommodate cognitive style. The validation instrument was used online using a google form which was carried out by 3 validators from junior high school science teachers in Tuban Regency. The instrument used is a validity sheet which includes material aspects, systematics, language, graphics, suitability with the stages of inquiry, and suitability with critical thinking indicators. Data were analyzed using a quantitative descriptive technique with a Likert scale as a result of the validation carried out by the validator. The results showed that the inquiry-based nutrition topic module to train critical thinking skills met very valid criteria with a mean score of 3.74. This module needs to be tested for its practicality and effectiveness in learning.Abstrak Modul topik nutrisi berbasis inkuiri dikembangkan agar dapat digunakan sebagai salah satu alternatif media pembelajaran inovatif dan diharapkan dapat mengakomodasi kebutuhan belajar murid berdasarkan gaya kognitif. Penelitian ini bertujuan merancang modul topik nutrisi berbasis inkuiri untuk melatih keterampilan berpikir kritis yang valid. Penelitian ini menggunakan model penelitian dan pengembangan 4D namun hanya sampai pada tahap validitas produk. Tahap awal (define) dilakukan tes MFFT pada kelas VIIIA SMPN 2 Jenu didapatkan hasil 11 siswa bergaya kognitif reflektif dan 11 siswa bergaya kognitif impulsif. Berdasarkan hasil tes MFFT, desain modul topik nutrisi berbasis inkuiri dirancang dengan mengakomodasi gaya kognitif. Instrumen validasi digunakan secara online menggunakan google form yang dilakukan oleh 3 orang validator dari guru IPA SMP di Kabupaten Tuban. Instrumen yang digunakan adalah lembar validitas yang meliputi aspek materi, sistematika, kebahasaan, kegrafikaan, kesesuaian dengan tahapan inkuiri, dan kesesuaian dengan indikator berpikir kritis. Data dianalisis menggunakan teknik deskriptif kuantitatif dengan skala likert hasil validasi yang dilakukan oleh validator. Hasil penelitian menunjukkan modul topik nutrisi berbasis inkuiri untuk melatih keterampilan berpikir kritis telah memenuhi kriteria sangat valid dengan skor rerata 3,74. Modul ini perlu diuji kepraktisan dan keefektifannya dalam pembelajaran.